Hypersensitivity diseases: type 1 hypersensitivity - Waldmann, Herman (Henry Stewart Talks, 2021)
Classes of hypersensitivity diseases, Type I hypersensitivity disease, Type I hypersensitivity mechanism of action, Key cells involved in type I hypersensitivity, Evolutionary and physiological basis for type I hypersensitivity disease